Penerapan Konsep Therapeutic Space Pada Healing and Rehabilitation Center di Ubud, Kabupaten Gianyar, Bali: Bahasa Indonesia - I Gede Damarutha Adrian Nugraha Arsitektur; I Wayan Wirya Sastrawan; Ni Putu Ratih Pradnyaswari Anasta Putri; Ni Komang Indra Mahayani (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Mental disorders are a condition of a person who experiences deviations in the person's thinking process, feelings and behavior. In Bali, especially in the Ubud area which is a tourism area in Bali, efforts have been made to deal with mental health cases. However, unfortunately, the number of rehabilitation facilities for mental health in Bali is less visible, when compared with rehabilitation facilities for narcotics and social rehabilitation. Therefore, the author attempts to design a container or building called the "Healing and Rehabilitation Center" which can provide consultations to patients using a visual healing method known as the "therapeutic space" concept which emphasizes the healing process in the built environment and continuity with nature. surroundings. The research method used by the author to compile this research is a qualitative method in the form of literature study, observation, documentation, interviews. The literature studies used as writing references include previous study journals, e-book sources and several precedent studies on similar buildings. The results of this research will show an innovation in the form of a new concept as well as proving the concept of Therapeutic Space which is implemented in various parts of building objects, both external and internal spaces which are used as part of physical and psychological therapeutic processes